Christine - Bensi, Danny ca. 20. Jh; Jurriaans, Saunder 1977- (Universum Film GmbH, 2018)
"The story of Christine Chubbuck, a 1970s TV reporter struggling with depression and professional frustrations as she tries to advance her career." [imdb.com]
Bildformat 1.85:1 (16:9 anamorph)
Original: Großbritannien, USA 2016
Keywords: Film; DVD-Video